Endoscopic Biliary Stenting for Portal Biliopathy Perforating Paracholedochal Collateral: A Rare Complication - Goyal, Kartik; Hussain, Sabir; Garg, Pawan Kumar; Bhargava, Narender; Varshney, Vaibhav Kumar (Journal of Digestive Endoscopy, 2019)
Extrahepatic portal venous obstruction (EHPVO) usually presents with upper gastrointestinal bleed in the first decade. Symptomatic portal hypertensive biliopathy is seen in minority of patients with EHPVO. With the use of endoscopic intervention, biliary drainage is maintained in these patients. Various procedural complications have been linked while performing endoscopic retrograde cholangiography and stenting; however, these are managed conservatively. Here, we are highlighting a case of EHPVO with symptomatic portal biliopathy who bled from paracholedochal collateral after biliary stenting and managed successfully with multidisciplinary approach.
Keywords: Extra-hepatic portal venous obstruction; paracholedochal plexus; portal biliopathy; stent